The Effect of Using the Student Facilitator and Explaining (SFE) Learning Model Assisted by Concrete Media on the Ability to Understand Science Concepts in Class V Students - Andika Aji Setiawan; Ari Suryawan; Tria Mardiana (Berpusi Publishing, 2023)
The purpose of this study was to examine the effect of using the Student Facilitator and Explaining (SFE) learning model assisted by concrete media on the ability to understand science concepts. The sample used was fifth grade students at SDN Pasuruhan 1, Mertoyudan District, Magelang Regency, totaling 29 students. Samples were taken using saturated sampling technique. This research method uses a pre-experimental method, namely the One Group Pretest-Posttest design. Data collection used an essay type test to measure students' understanding of concepts. This test is used to determine the ability to understand the concept before and after treatment. From the results of the study showed that the average result of the students' pretest was 57.5% and the average result of the students' posttest was 83.6%. The hypothesis test used was the paired sample t test with sig. of 0.000 and smaller than the significance level of 0.05. So it can be concluded that the use of the Student Facilitator and Explaining (SFE) model assisted by concrete media has an effect on students' understanding of science concepts.